Bottom-up precise synthesis of stable platinum dimers on graphene - Huan Yan (Nature Portfolio, 2017)
Controlled fabrication of few-atoms supported catalysts is a major challenge in the synthesis of nanomaterials. Here, the authors show a bottom-up approach to precisely synthesize platinum dimers supported on graphene, which display higher catalytic activity and stability than single atoms and nanoparticles.